Factors associated with SARS-CoV-2 RNAemia development at COVID-19 diagnosis - Javier Martín-Escolano; Ana Ruiz-Molina; Cristina Rodríguez-Urbistondo; Carmen Infante-Domínguez; Gabriela Abelenda-Alonso; Gorane Euba; Zaira R. Palacios-Baena; Francisco Arnaiz-Revillas; Jorge Alba; Alexander Rombauts; Regino J. Rodríguez-Álvarez; Natalia Maldonado; et al. (PLoS ONE, 2025)
Objectives SARS-CoV-2 RNAemia at diagnosis is associated with mortality. The aims were to identify factors associated with the development of RNAemia. Methods Multicenter COVID-19 cohort study was conducted between January 2020 and May 2023. Demographics, chronic underlying diseases, symptoms and signs, analytical and radiological variables, cytokines, and neutralizing antibodies were evaluated on admission. RNAemia was the primary endpoint. Results We included 1011 patients, 392 (38.8%) immunocompromised and 619 (61.2%) immunocompetent. RNAemia occurred in 49.7% and 18.7% (p < 0.001), respectively, being independently associated with 30-day all-cause mortality. In immunocompromised patients, factors independently associated with RNAemia were Alpha and Omicron VOC periods (OR: 1.95 [1.01–3.79]), pneumonia (OR: 1.96 [1.10–3.50]), LDH > 300 UI/L (OR: 1.64 [1.02–2.63]) and neutralizing antibodies absence (OR: 2.51 [1.57–4.00]). In immunocompetent patients, the factors associated with RNAemia were Delta and Omicron VOC periods (OR: 2.27 [1.46–3.52]), lymphocyte count < 1000/µL (OR: 1.81 [1.16–2.80]) and LDH levels > 300 IU/L (OR: 3.99 [2.51–6.36]). Conclusions Immunodeficiency almost tripled SARS-CoV-2 RNAemia. Omicron VOC period, LDH as inflammatory biomarker, and a lower immune response in all patients, neutralizing antibodies absence in immunocompromised and lymphopenia in immunocompetent, and pneumonia in immunocompromised patients were associated with RNAemia.